2021
DOI: 10.3389/fnagi.2021.756241
|View full text |Cite
|
Sign up to set email alerts
|

Lateralized Contributions of Medial Prefrontal Cortex Network to Episodic Memory Deficits in Subjects With Amnestic Mild Cognitive Impairment

Abstract: Both episodic memory and executive function are impaired in amnestic mild cognitive impairment (aMCI) subjects, but it is unclear if these impairments are independent or interactive. The present study aimed to explore the relationship between episodic memory deficits and executive function deficits, and the underlying functional mechanisms in aMCI subjects. Thirty-one aMCI subjects and 27 healthy subjects underwent neuropsychological tests and multimodal magnetic resonance imaging (MRI) scans. Hippocampal netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…The medial prefrontal cortex (mPFC) has abundant connections with other cortical and subcortical regions, which makes it as an essential cortical region for integrating information from other areas and converging updated information to other areas in the brain ( 35 ). Take into consideration of its crucial role in the cognitive process including attention, working memory, spatial learning and emotional response, dysfunction of mPFC has been found in various psychiatric and neurological disorders with cognitive impairment ( 36 , 37 ). Post-chemotherapy lung cancer patients exhibited decreased FC in the left mPFC when compared with non-chemotherapy lung cancer patients ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The medial prefrontal cortex (mPFC) has abundant connections with other cortical and subcortical regions, which makes it as an essential cortical region for integrating information from other areas and converging updated information to other areas in the brain ( 35 ). Take into consideration of its crucial role in the cognitive process including attention, working memory, spatial learning and emotional response, dysfunction of mPFC has been found in various psychiatric and neurological disorders with cognitive impairment ( 36 , 37 ). Post-chemotherapy lung cancer patients exhibited decreased FC in the left mPFC when compared with non-chemotherapy lung cancer patients ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have previously found varying degrees of EMN impairment in the AD spectrum, which lead to cognitive decline (Cai et al, 2017;Cassady et al, 2021;Liang et al, 2022). Moreover, Ye et al (2021) found a correlation between EF and EMN (F. Bai et al, 2016). However, whether EF influences EMN, thereby mediating EM function, remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al (2016) highlighted EF as a key predictor for aMCI to AD conversion, with impaired EF exacerbating EM defects and increasing the risk of progression to AD. Ye et al (2021) suggested that the EM defects in aMCI may be partially due to impaired EF. However, the mechanism by which EF in aMCI patients affects EM…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations